Association between Premenstrual Tension Syndrome and Menstruation Distress with Physical Activity - Iqra Tul Hussain; Amena Batool; Ayesha Iftikhar (The Sky, 2023)
This study explores the association between physical and recreational activities, length of menstrual flow and interpersonal bonds with premenstrual tension symptoms and correlation of stress with physical activity levels among women. Analytical study was conducted on 71 Premenstrual Tension Syndrome (PMTS) women with a history of dysmenorrhea and stress presented at least 1-2 weeks premenstrual; reported at least for two consecutive menstrual cycles excluding women with tumors, gynecological and endocrinological disorders. The study was conducted from (May to October 2022) at Basic Health Unit (Vario, Sialkot). A Modified Moos Menstrual Distress questionnaire (MDQ) and a self-designed questionnaire were used to collect the data. Results were analyzed using SPSS software 22 version. Mean age was 24.01±4.062 years (N=53, 74.6%) of participants were unmarried whereas (N=18, 25.44%) were married. Length of menstrual flow days was reported as 3 to 5 days (N= 33, 46.5%). Participants (N=41, 57.7%) had severe PMTS with (N=47, 66.2%) preferring to isolate themselves as interference of the symptoms, (N= 43, 60.6%) had stress eating. Chi-square test was observed for the PMTS symptom of pain with recreational and levels of physical activity (p=0.003 0.05); (p=0.00), Impaired concentration (p=0.001 0.05); (p=0.012) and negative effects (p=0.034 0.05); (p=0.02) whereas no significant association was found for behavior, autonomic reactions and water retention symptoms. Length of menstrual flow (p=0.009) and working activities (p=0.025) were correlated (p-value 0.05 ) with physical activity. However, Spear's man correlation between physical activity level and PMTS-induced stress had a weak correlation (p=0.036). Recreational and active levels of physical activity effectively reduce the severity of premenstrual tension symptoms.